Female virtual intrasexual competition and its consequences: An evolutionary mismatch perspective - YONG, Jose C. (Institutional Knowledge at Singapore Management University, 2017)
Intrasexual competition is a key component of sexual selection. Evolutionarily, women compete for access to and retention of mates on key dimensions that men have evolved to value and prioritize in their long- and short-term mates, in particular physical attractiveness. Such competition evolved to be adaptive in ancestral environments as the perceived competition consisted of real individuals. However, underlying psychological mechanisms for competition are excessively triggered and more continuously engaged in modern environments, because these psychological mechanisms for social comparison and competition, at a deep level, do not differentiate between real people and imagined intrasexual competition in the form of mass media images. Utilizing an evolutionary mismatch framework, this chapter explores ways that women are psychologically influenced by the pervasive presence of virtual same-sex competitors for mates. Various negative psychological states in modern societies (e.g., depression, eating disorders) may be linked to virtual intrasexual competition.